(untitled) (World Economics and Finance Bulletin, 2022)
The banking sector in Iraq faces many challenges, and from a diagnostic and analytical view of the overall economic situation of the country, the conditions that the country is going through are directly reflected on the banking sector in the Iraqi economy, and given the prominent role of international financial reporting standards as they work to identify and measure the financial events of banks, And compliance with the standards leads to achieving value and achievement for its customers and stakeholders on a larger scale, as banks can achieve the targeted results for them, leading to increased customer satisfaction and an increase in their value in the long run. Accordingly, the research aimed to define the international financial reporting standards IFRS and the strategic financial performance, and to clarify the extent of compliance with the international financial reporting standards IFRS and its impact on the strategic financial performance, as compliance with the international financial reporting standards IFRS has a significant impact on the strategic financial performance. For the purpose of achieving the goal of the research, a group of private local banks that apply the International Financial Reporting Standards (IFRS) were selected, the research sample, and the questionnaire method was used for the purpose of collecting data from the sample members mentioned, and an analysis of the data collected was statistically performed using the SPSS program